EXPERIENCE OF CHAPLAINCY SERVICE IN THE ARMED FORCES OF LEADING COUNTRIES OF THE WORLD - Tereshchuk, Oleksii (Honor and Law, 2025)
The article examines the peculiarities of organizing military chaplaincy activities in the armed forces of leading countries worldwide. It identifies the key principles for meeting the spiritual and religious needs of service members, which form the foundation for the establishment and functioning of the chaplaincy institution in the Armed Forces of Ukraine.